Improved physical control of glyphosate‐resistant Italian ryegrass (Lolium multiflorum) on rice paddy levees in Japan. Issue 2 (12th May 2017) - Handayani, Valentina Dwi Suci; Tanno, Yuki; Yamashita, Masayuki; Tobina, Hiroyuki; Ichihara, Minoru; Ishida, Yoshiki; Sawada, Hitoshi
Abstract : Italian ryegrass ( Lolium multiflorum Lam.) is a non‐native annual winter grass that has seriously infested rice paddy levees and wheat fields in Japan. Recently, glyphosate‐resistant Italian ryegrass was found on paddy levees in central Japan, thereby making control of the grass by using glyphosate less effective. In this study, physical control methods were tested that combined the timing and frequency of mowing in order to more effectively control glyphosate‐resistant Italian ryegrass on rice paddy levees. A 3 year field experiment was conducted from 2012 to 2014 in a western region of Shizuoka Prefecture, where glyphosate‐resistant Italian ryegrass has become dominant. Five treatments were tested: (i) mowing once before the flowering of the grass (i.e. conventional mowing measure); (ii) mowing once during flowering; (iii) mowing twice during flowering; (iv) glyphosate application before flowering (i.e. one of the conventional mowing measures); and (v) no treatment. The above‐ground biomass, seed production, soil seed bank and seedling occurrence of Italian ryegrass were measured to determine the effectiveness of these treatments. Mowing during the flowering period resulted in reduced above‐ground biomass, seed production and soil seed bank when compared with the other treatments. Additionally, mowing twice during the flowering period resulted in a lower seedling density than mowing once. The results suggest that, in this region, physical control by mowing during the flowering period would be more effective than conventional measures for controlling glyphosate‐resistant Italian ryegrass.